Enhanced caspase-8 recruitment to and activation at the DISC is critical for sensitisation of human hepatocellular carcinoma cells to TRAIL-induced apoptosis by chemotherapeutic drugs - Ganten, Tom M.; Haas, Tobias L.; Sykora, Jaromir; Stahl, Heiko; Sprick, Martin; Fas, Stefanie C.; Krueger, Andreas; Weigand, Markus A.; Grosse-Wilde, Anne; Stremmel, Wolfgang; Krammer, Peter H.; Walczak, Henning (Cell death and differentiation)
Tumour necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) exhibits potent antitumour activity upon systemic administration in mice without showing the deleterious side effects observed with other apoptosis-inducing members of the TNF family such as TNF and CD95L. TRAIL may, thus, have great potential in the treatment of human cancer. However, about 60% of tumour cell lines are not sensitive to TRAIL. To evaluate the mechanisms of tumour resistance to TRAIL, we investigated hepatocellular carcinoma (HCC) cell lines that exhibit differential sensitivity to TRAIL. Pretreatment with chemotherapeutic drugs, for example, 5-fluorouracil (5-FU), rendered the TRAIL-resistant HCC cell lines sensitive to TRAIL-induced apoptosis. Analysis of the TRAIL death-inducing signalling complex (DISC) revealed upregulation of TRAIL-R2. Caspase-8 recruitment to and its activation at the DISC were substantially increased after 5-FU sensitisation, while FADD recruitment remained essentially unchanged. 5-FU pretreatment downregulated cellular FLICE-inhibitory protein (cFLIP) and specific cFLIP downregulation by small interfering RNA was sufficient to sensitise TRAIL-resistant HCC cell lines for TRAIL-induced apoptosis. Thus, a potential mechanism for TRAIL sensitisation by 5-FU is the increased effectiveness of caspase-8 recruitment to and activation at the DISC facilitated by the downregulation of cFLIP and the consequent shift in the ratio of caspase-8 to cFLIP at the DISC.
Gesehen am 04.03.2021